Immune recovery in HIV-infected patients after Candida esophagitis is impaired despite long-term antiretroviral therapy. (31st July 2016) - Stuehler, Claudia; Bernardini, Claudia; Elzi, Luigia; Stoeckle, Marcel; Zimmerli, Stefan; Furrer, Hansjakob; Günthard, Huldrych F.; Leibundgut-Landmann, Salomé; Battegay, Manuel; Khanna, Nina
Abstract : Objective: Candida esophagitis belongs to the most common AIDS-defining diseases; however, a comprehensive immune pathogenic concept is lacking. Design: We investigated the immune status of 37 HIV-1-infected patients from the Swiss HIV cohort study at diagnosis of Candida esophagitis, 1 year before, 1 year later and after 2 years of suppressed HIV RNA. We compared these patients with three groups: 37 HIV-1-infected patients without Candida esophagitis but similar CD4 + cell counts as the patients at diagnosis (advanced HIV group), 15 HIV-1-infected patients with CD4 + cell counts higher than 500 cells/μl, CD4 + cell nadirs higher than 350 cells/μl and suppressed HIV RNA under combination antiretroviral therapy (cART) (early cART group) and 20 healthy individuals. Methods: We investigated phenotype, cytokine production and proliferative capacity of different immune cells by flow cytometry and enzyme-linked immunosorbent spot. Results: We found that patients with Candida esophagitis had nearly abolished CD4 + cell proliferation in response to Candida albicans, significantly increased percentages of dysfunctional CD4 + cells, significantly decreased cytotoxic natural killer cell counts and peripheral innate lymphoid cell counts and significantly reduced IFN-γ and IL-17 production compared with the early cART group and healthy individuals. Most of these defects remained for more than 2 years despite viral suppression. The advanced HIV group without opportunistic infection showed partly improved immune recovery. Conclusion: Our data indicate that Candida esophagitis in HIV-1-infected patients is caused by an accumulation of multiple, partly Candida -specific immunological defects. Long-term immune recovery is impaired, illustrating that specific immunological gaps persist despite cART. These data also support the rationale for early cART initiation to prevent irreversible immune defects. Abstract : Supplemental Digital Content is available in the text